Prognostic Significance of Neutrophil-to-Lymphocyte Ratio and C-Reactive Protein/Albumin Ratio in Luminal Breast Cancers With HER2-Negativity - Chen, Fei; Chen, Danzhi; Jin, Lidan; Xu, Chenpu; Zhao, Wenhe; Hu, Wenxian (Frontiers in Oncology, 2022)
Purpose This study was determined to evaluate the prognostic value of neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein/albumin ratio (CAR) prior to surgery in luminal breast cancers (BC) with HER2-negativity. Methods The clinical data of 708 HER2-negative luminal BC patients from January 2013 to December 2016 were retrospectively collected and analyzed. The optimal cut-off value of NLR and CAR were determined via receiver operating characteristic (ROC) curve. The disease-free survival (DFS) and cancer specific survival (CSS) rates were estimated using the Kaplan−Meier method. Cox univariate and multivariate proportional hazards regression models were performed to identify significant predictors of DFS and CSS simultaneously. Results The mean age of the patients diagnosed was 52.43 years (range, 15–95 years), and the median follow-up was 62.71 months (range, 12-92 months). Univariate and multivariate analysis confirmed that NLR ≥2.2 was significantly associated with worse DFS (HR=2.886, 95%CI=1.756-4.745, p<0.001), and same results were obtained in terms of CSS (HR=3.999, 95%CI=2.002-7.987, p<0.001). Similarly, CAR ≥0.07 was independently and significantly associated with poor DFS (HR=3.858, 95%CI=2.346-6.345, p<0.001) and CSS (HR=6.563, 95%CI=3.558-12.106, p<0.001). Conclusion Preoperative evaluation of NLR and CAR were significant and independent prognostic indicators for luminal breast cancers with HER2-negativity.